The Core Health Science Library in Canada - Huntley, June Leath (1974)
Core lists in Canada are characterized by regional differences. The lists of current importance are: (1) the British Columbia acquisitions guide for hospital libraries, (2) three Saskatchewan lists for hospitals of different sizes, (3) a core list recommended for Ontario hospitals, (4) Quebec core lists, including French language lists.